Statistical methods for evaluating safety in medical product development - Gould, Lawrence (A. Lawrence) (Statistics in practice., 2014)
This book gives professionals in clinical research valuable information on the challenging issues of the design, execution, and management of clinical trials, and how to resolve these issues effectively. It also provides understanding and practical guidance on the application of contemporary statistical methods to contemporary issues in safety evaluation during medical product development. Each chapter provides sufficient detail to the reader to undertake the design and analysis of experiments at various stages of product development, including comprehensive references to the relevant literature.-Provides a guide to statistical methods and application in medical product development -Assists readers in undertaking design and analysis of experiments at various stages of product development -Features case studies throughout the book, as well as, SAS and R code.